Thermodynamic Assessment of High Entropy (Fe-Mn) Binary Alloy System Using Calphad Method: DOI: 10.48129/kjs.11303 - shah, Waseem Ullah; mamalis, A.G MAMALIS; YIN, HAI QING YIN; Khan, Dil Faraz (Kuwait Journal of Science, 2022)
This paper reports thermodynamic calculations and predictions of Meta stable binary alloy Fe-Mn system using Calphad approach. Thermodynamic analysis involves calculation of phase diagram, Gibbs energy of mixing, excess Gibbs energies, thermodynamic molar activities, and coefficient of activities, partial and integral values of enthalpy for Co-Fe alloy system at three elevated temperatures 1200K, 1225K, and 1250K. The alloy reports positive deviation from vegard,s law and corresponding good negative deviation from Rout’s law ideal Gibbs curve. Predicted by results that the ferromagnetic state of Mn-Fe alloy is the most stable and ground state. Investigated results reports many magnetic based moments of atoms. For Mn and Fe system, their measured phase equilibria shows activity curve data for solid in almost ideal behavior, but somehow small positive deviation from ideality